Observation of changes in limited distance using The configuration of compression spring and load cell as an alternative measurement of narrow displacement - Purnama, Prima Jovita Permata Dinasty (2016)
The use of digital measuring devices is replacing various conventional or analog devices. Measuring displacement usually using caliper, accuracy is the main issue to obtain precise data. The use of sensor is one of the solutions to make digitized. This research conducted in observations of the distance changes on the compression spring that is placed on load cell. This research is using a mechanism where the spring length changing caused by compressive force. It can be sensed and measured digitally by Arduino base system and displayed using LCD 2x16. Data from sensor need gained before process using HX711. This measurement using three types of wire diameter, 0.7 mm, 0.8 mm, and 1 mm and three push buttons as an input. Some testing conducted to get the data of set point, accuracy, repeatability, reproducibility, and hysteresis. Each testing conducted more than one to get the precious data. Before the measurement, determining the set point is required to obtain a constant value of spring. Accuracy of all the spring is 0.14 mm until 0.72 mm. The hystereses observed are 0.29 mm in manual measurement and 0.15 mm in digital measurement of spring A. For spring B: 0.08 mm and 0.1 mm and in spring C: 0.11 mm and 0.1 mm. Spring A have deviation < 1 mm in measurement distance < 40 mm, while spring B have deviation < 1 mm in distance < 60 mm, and displacements < 50 mm for spring C. Spring A, B and C do not have linear deviation. It decreases after 20 mm measurement distance then increase. Some advantages of this measurement are on the accuracy, ease of use, spring replacement is possible, and also have better display.